Exploitation of sweet lemon residues in the production of essential oils - Khalid, Khalid A. (2021)
The content of EO (%) was higher in peels than in flowers or leaves. Citronellal, nerol, and limonene were the major constituents of EO extracted from leaves, flowers, and peels, respectively. All detected components of various oils belonged to four chemical fractions (monoterpene hydrocarbons (MH), oxygenated monoterpenes (OM), sesquiterpene hydrocarbons (SH), and oxygenated sesquiterpenes (OS)). The MH was the major faction of peel EO while the OM was the major fraction of leaf and flower EOs. The SH and OS were formed as the minor fractions in all EOs.